Expression Analysis of α5 Integrin Subunit Reveals Its Upregulation as a Negative Prognostic Biomarker for Glioblastoma - Nelly Etienne-Selloum; Julien Prades; Diana Bello-Roufai; Mathieu Boone; Henri Sevestre; Stéphanie Trudel; Pascal Caillet; Alexandre Coutte; Christine Desenclos; Jean-Marc Constans; Sophie Martin; Laurence Choulier; et al. (MDPI AG, 2021)
Integrin α5β1 was suggested to be involved in glioblastoma (GBM) aggressiveness and treatment resistance through preclinical studies and genomic analysis in patients. However, further protein expression data are still required to confirm this hypothesis. In the present study, we investigated by immunofluorescence the expression of integrin α5 and its prognostic impact in a glioblastoma series of patients scheduled to undergo the Stupp protocol as first-line treatment for GBM. The integrin α5 protein expression level was estimated in each tumor by the mean fluorescence intensity (MFI) and allowed us to identify two subpopulations showing either a high or low expression level. The distribution of patients in both subpopulations was not significantly different according to age, gender, recursive partitioning analysis (RPA) prognostic score, molecular markers or surgical and medical treatment. A high integrin α5 protein expression level was associated with a high risk of recurrence (HR = 1.696, 95% CI 1.031-2.792, p = 0.0377) and reduced overall survival (OS), even more significant in patients who completed the Stupp protocol (median OS: 15.6 vs. 22.8 months; HR = 2.324; 95% CI 1.168-4.621, p = 0.0162). In multivariate analysis, a high integrin α5 protein expression level was confirmed as an independent prognostic factor in the subpopulation of patients who completed the temozolomide-based first-line treatment for predicting OS over age, extent of surgery, RPA score and O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation (p = 0.029). In summary, for the first time, our study validates that a high integrin α5 protein expression level is associated with poor prognosis in GBM and confirms its potential as a therapeutic target implicated in the Stupp protocol resistance.